In Memory Of Prof. N. A. Jafarey (1929-2015) - Ejaz A Vohra (ziauddin University, 2024)
May his soul rest in peace Prof Naeem Jafarey was well known for his status as pioneer in medicine and eminent pathologist when he joined as director of postgraduate studies at the newly established Dr Ziauddin postgraduate institute of medical sciences. He was born on 4thof May 1929, in Allahabad in India, to an illustrious family. He graduated from King Edward Medical College in Lahore in 1955, the prestigious and the oldest institution in Pakistan. He showed his inclination towards medical research when he joined Mayo Hospital as medical officer of Pakistan Medical and research council in Lahore. He subsequently moved to USA and was trained at New York State University and obtained certification of American Board of Pathology. He retired as professor of pathology from Jinnah Postgraduate Center (JPMC) and he was also one of the founding members of Basic Medical Sciences institute at JPMC, which was established with collaboration with University of Alabama, USA. He retired from JPMC in 1989...